Womens work: the Measurement and the Meaning - Bould,Sally (2008)
Understanding the meaning of a womans economic activity requires an in depth understanding of the labour force concept and how it has been applied to women. This paper will examine in detail some of the issues and problems with the data available and its usage as well as the problem of cross national comparability. These issues will be explored by a close examination of the International Labour Organizations (ILO) recommendations and definitions and yearly statistics (http://laborsta.ilo.org/). The first part of the paper will focus on the development of the labour force concept and a history of how womens labour force participation has changed in the last 30 years using the examples of Bangladesh and Thailand. A different historical picture is found in the four European countries examined: Portugal, Spain, Belgium and France. The second part of the paper will examine factors which need to be taken into account in forming a broader understanding of womens work in these European countries. Age, education, working hours, wages, and motherhood are examined. In view of this analysis the paper will critique the European Union goal of 60% of women working in EU countries by 2010.